PENGARUH FERMENTASI MENGGUNAKAN BERBAGAI MACAM RAGI TERHADAP KUALITAS TEPUNG BULU AYAM - Nautus Stivano Dalle (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2022)
This study aims to determine the influence of the use of various kinds of yeast as a fermentation medium for chicken feather flour. The chicken feather waste used is broiler chicken feather waste from the Ruteng Inpres Market, Central Manggarai Regency. The method used in this study was an experimental method and the fermentation results were analyzed at the Feed Chemistry Laboratory of the Faculty of Animal Husbandry, Marine and Fisheries, Nusa Cendana University. The design used was a complete randomized design with 4 treatments and 3 tests. The treatment tested was R0: Chicken feather flour (CFF); R1: fermented chicken feather flour (FCFF) Saccharomyces cerevisiae; R2: TBAT Amylomyce rouxii; R3: FCFF Rhizopus oligosporus. Variables measured in this study are organoleptic tests in the form of aroma, texture and color as well as proximate tests to see the nutritional quality of chicken feather flour. The results showed that the treatment had a significant effect on reducing the nutritional content of chicken feather flour. Based on the results of this study, the best fermentation medium is to use baker's yeast.